Groundwater Flooding on Atolls Caused by Storm Surges: Effects of the Dual‐Aquifer Configuration - Satoshi Tajima; Philip Brunner; Jiaqi Liu; Hugo Delottier; Tomochika Tokunaga (Water Resources Research)
Abstract Storm surges associated with tropical cyclones endanger atolls through groundwater flooding, where groundwater is discharged from the land surface as the sea level rises. Atolls are characterized by a “dual‐aquifer” configuration, where recent Holocene sediments unconformably overlie highly permeable Pleistocene limestone, creating an interface called a “Thurber discontinuity.” This study aimed to quantitatively analyze how the dual‐aquifer configuration of atolls controls the temporal dynamics of groundwater flooding caused by storm surge. To this end, we ran surface‐subsurface coupled synthetic numerical simulations using HydroGeoSphere and compared 12 scenarios with different Thurber discontinuity elevations and hydraulic conductivities of the Pleistocene aquifer (KP). The results showed that the shallower the Thurber discontinuity and the higher the KP value, the higher the maximum water depth in the freshwater swamp on the atoll during the storm surge and the longer the flooding duration. Despite the effects of the different dual‐aquifer configurations, the initial water table elevation and salinity distribution were almost identical in all the simulation cases. These findings suggest that accurate information on the dual‐aquifer configuration is necessary to evaluate the potential risk of groundwater flooding on atolls accompanying storm surges. Furthermore, the results indicate that groundwater flooding caused by storm surges substantially contributes to cyclone‐driven flooding on atolls, and hence, it should not be neglected in flood predictions to avoid underestimation.